Diskursus Tasawuf Di Barat (Membaca Pemikiran Martin Lings) - Hakiki, Kiki Muhamad; Idrus, Diparakhmawan Al (AL-ADYAN, 2018)
The focus of this study was to study the "Tasawuf Discourse in the West by focusing on Martin Lings' s suicidal thoughts". After studying and analyzing Martin Lings's thinking, as outlined above, it is possible to draw some of the following conclusions: 1). In Ibn `Arabī's view there is one; the form of God is nature and nature is God. There is nothing in existence except God, everything other than God, none in itself, it is merely a manifestation of God's existence, nature is God's reflection, existence is a loan originating with God. God and nature are one but different. The concept of Wahdāt al-Wujūd is emphasized on both sides as tasybih and also tanzih. God is seen from the side of nature, then He is identical with nature, but from the perspective of God, He is different from nature at all, because He is an infinite substance beyond the physical realm. "Huwa La Huwa" ("She and not him"). This unity and purity are the principles of coincidentiaoppositorum in the ontologism of the Unity (az-zahīr) and the Bathin (al-bathīn), between the Awwal (al-awwāl) and the Last (al-akhīr), between the One (al -wahīd) and the Many (al-kasīr) and between inequality (tanzīh) and similarity (tasybīh). The transcendent God (munazzah) is seen in terms of His substance, the hidden and the one. But when viewed in the name of His name, the immanent God (musyabbah), the one and the hidden one reveals Himself by His name. 2). The doctrine of al-wujdd al-wujūd according to Martin Lings is a belief that believes that there is only Wujūd Hakiki. The true wujūd belongs to God alone, whereas He is called the wujūd of illusion. God blesses every one of His creations that look different or plural.